2011
DOI: 10.4025/actasciagron.v33i4.11160
|View full text |Cite
|
Sign up to set email alerts
|

Simulate rain about action insecticide flonicamid in the control of the cotton aphid

Abstract: ABSTRACT. The cotton production system in Brazil concentrates on the area of the cerrado, characterized by frequent rains that interfere in the effectiveness of the necessary sprays during its cycle. The objective of the work was to evaluate simulate rain of 15 mm in 4 hours after spraying in the control of Aphis gossypii with insecticide flonicamid. Plants of Gossypium hirsutum were cultivated in pots containing soil as substrate in greenhouse conditions. The pots were arranged in randomized complete design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…This implies the need for a new spray that will restore the quantity of leachate products, resulting in higher costs. Some studies involving other cultures and spraying liquids have demonstrated that rains of low intensity and short intervals after spraying are sufficient to compromise the effectiveness of the plant protection treatment, making the use of certain adjuvants critical (MATEUS et al, 2004;GASKIN & STEELE, 2009;PANNACCI et al, 2010;FORTUNATO et al, 2011;ECHER & ROSOLEN, 2012).…”
Section: Spraying Liquid Deposits After Intervals Of Artificial Rainmentioning
confidence: 99%
“…This implies the need for a new spray that will restore the quantity of leachate products, resulting in higher costs. Some studies involving other cultures and spraying liquids have demonstrated that rains of low intensity and short intervals after spraying are sufficient to compromise the effectiveness of the plant protection treatment, making the use of certain adjuvants critical (MATEUS et al, 2004;GASKIN & STEELE, 2009;PANNACCI et al, 2010;FORTUNATO et al, 2011;ECHER & ROSOLEN, 2012).…”
Section: Spraying Liquid Deposits After Intervals Of Artificial Rainmentioning
confidence: 99%
“…Rainfall is a significant factor that affects the efficacy of pesticides for pest control in fruit crops. Rainfall can adversely affect the effectiveness of pesticide treatments, increasing the need for reapplications, consequently increasing production costs and environmental impacts (Fortunato et al, 2011). The effects of rainfall on pesticide application have been studied using rainfall simulators to provide information that contributes to the improvement of application technologies and persistence of pesticide residues on plants (Taylor & Mathews, 1986;Decaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A ação da água pode remover parte do produto da folha, reduzindo sua absorção e o período de proteção (DINARDO-MIRANDA et al, 2004). O inseticida fl onicamida tem sua efi cácia reduzida quando ocorrem precipitações primeiras quatro horas após a pulverização (FORTUNATO et al, 2011). Entretanto, os inseticidas têm comportamentos diferentes em relação à infl uência das precipitações pluviométricas, devido, principalmente, a características intrínsecas dos produtos e a sua formulação (MASHAYA, 1993).…”
Section: Introductionunclassified